Elasticities of resource- use in fish production: A case study of Oyo agricultural zone, Oyo State (2009)
This paper examined the elasticities of resource use in fish production in Oyo agricultural zone, Oyo state. The data used is from a primary source. The instruments of data collection were structured questionnaire and in-depth interview. Multi-stage sampling technique was employed to sample 120 fish farmers. However, only 100 respondents were valid and used in the final stage of this work. Descriptive, Gross Margin Analysis (GM) and inferential statistics (production function) were employed in the analysis of the data. The results of the analysis shows that labour, number of fingerlings, feed, fertilizer and years of experience contribute to increase in fish output, while age of the pond, area of the pond, lime and production period decrease the fish output in the study area. However, the total sum of elasticities of production of the variables was greater than unity that is 1.97